Pinning down a moving target: sustainability, people and forests - Prabhu, Ravi; Vanclay, J.K. (1997)
Sustainability in the context of development and forest management is a concept defined by human-beings. As human needs change across space and time, so will the expectations of what benefits and services of forests need to be sustained. Much of CIFOR's research focuses on providing a better understanding of what the key-issues are that drive the management of forests, and how they might be influenced to provide sustainable solutions. Two complementary approaches to better understanding the key-issues and the dynamics of managing forests are the subject of this presentation. In the first approach CIFOR is seeking to identify the key-issues in terms of Criteria and Indicators for sustainable forest management, with the objective of developing better assessment methods. The second approach is based on modelling the interactions of human-beings and forests. Both approaches illustrate the need to develop tools that are sufficiently generalisable to be useful for a large number of people, but also sufficiently adaptable to local conditions for them to have practical utility.